Assessment of a prototype implantable cardioverter for ventricular tachycardia. Relation between synchronisation of sensing and origin of the tachycardia. - Perelman, M S (1984)
The feasibility of internal cardioversion for ventricular tachycardia using a prototype of an implantable cardioverter which delivers a low energy discharge via an intracardiac lead and its acceptability to the patient were studied. The cardioverting discharge was synchronised to the apical right ventricular electrogram. In 29 episodes of ventricular tachycardia (RR interval 250-700 ms) the apical electrogram was reliably sensed. The interval from the onset of the QRS complex to the marker of sensing of the electrogram was significantly greater in the 15 episodes arising from the left ventricle than in the 14 episodes arising from the right ventricle; in three cases of ventricular tachycardia arising from the left ventricle the interval exceeded 100 ms. In all cases except one, however, sensing occurred within the first 80% of the QRS complex. In two episodes (RR interval 150 and 190 ms--that is, less than the refractory period of the unit) sensing of the electrogram was unreliable. The unit successfully terminated 10 of 15 episodes of ventricular tachycardia using energies ranging between 0.01 and 1.0 J, but 19 of the 23 discharges delivered to conscious patients caused varying degrees of discomfort. Sensing within 100 ms of the onset of the QRS complex (-20% to 83% of QRS) permitted effective and safe termination of ventricular tachycardia. Although there was neither acceleration of tachycardia nor ventricular fibrillation, subthreshold discharges advanced the next local ventricular electrogram in seven instances. An external low energy cardioverter connected to an intracardiac lead is a useful alternative to repeated external direct current shocks.